“E-Motional Navigators”: Italian Adaptation and Validation of the Socio-Emotional e-Competencies Questionnaire (e-COM) - C. Cricenti; G. Lausi; B. Barchielli; E. Mari; J. Burrai; A. M. Giannini; A. Quaglieri (Human Behavior and Emerging Technologies)
Given the importance of social–emotional skills in fostering highly prosocial behaviors and the increasing frequency by which relationships are established and maintained in cyberspace, several studies have been conducted focusing on the role of social-emotional skills developed in the online environment. However, the instruments developed to date have mainly considered “face-to-face” interactions, without considering the unique features of the virtual environment. The purpose of the present study was to validate the Italian translation of the Socio-Emotional e-Competencies Questionnaire. This instrument has been constructed to assess the knowledge, skills, and attitudes necessary to understand and manage emotions in the online environment for fostering positive relationships (e-competencies (e-COM)). The final sample consisted of 1096 adults (53.0% men) aged between 18 and 73 years. Factor analyses confirmed the original five-factor structure, which showed excellent fit indices (i.e., root mean square error of approximation (RMSEA), Tucker–Lewis index (TLI), and comparative fit index (CFI)). Correlation analyses with other instruments related to social–emotional competence (i.e., E-motions Questionnaire, Brief Emotional Intelligence Scale, and Difficulties in Emotion Regulation Scales) confirmed the convergent validity of the scale. Gender differences were also explored, in which women scored higher than men in all dimensions of e-COM except for emotional e-independence. Overall, this study demonstrated that the Italian version of e-COM is a reliable and valid tool for measuring social-emotional competence in a virtual context.